Kepentingan Terbaik Anak dalam Pengaturan Hukum Dispensasi Perkawinan - Kusnadi, Sekaring Ayumeida (Legal Standing : Jurnal Ilmu Hukum, 2025)
The state is constitutionally obligated to ensure the fulfillment of child protection rights as an integral part of human rights. One such regulatory mechanism pertains to the legal framework governing marital agreements, known as marriage dispensation. This legal document is used to deal with specific situations that are considered to be in the best interests of the child. Article 7, paragraph (2) of Law No. 16/2019 on Marriage says that marriage dispensation may be granted in cases of extreme urgency. However, the legal text does not clearly explain what "very urgent reasons" are. The objective of this study is to analyze the concept of the best interests of the child within the framework of the regulation of marriage dispensation in Indonesia. The results of this study will probably be used as a reference when the Marriage Law is changed in the future. The research method juridical normative within statute and conceptual approach. The results explain that there is a lack of clear legal guidelines regarding marriage dispensation, leading to different interpretations and contributing to the high number of marriage dispensation applications in Indonesia. The main reason people use these apps is emotional, and it has to do with love. This condition has the potential to circumvent the fundamental principle of child protection and undermine the legal objectives that are intended to be achieved. The recommendation in this article is that the Marriage Law should clearly define "very urgent reasons" for obtaining marriage dispensation in the future. This affirmation is needed to make sure that the law is clear, fair, and benefits children while protecting them. The main idea of this research is that the rules in the Marriage Law should be changed to match the ideas of protecting children and the idea that the child's best interests should be considered, as stated in international agreements like the Convention on the Rights of the Child, which has been ratified by Indonesia.